1995
DOI: 10.1017/s0003598x00081941
|View full text |Cite
|
Sign up to set email alerts
|

Horse, wagon & chariot: Indo-European languages and archaeology

Abstract: New discoveries across the steppe zone of eastern Europe, and new dates relating to those discoveries, keep that oldest of archaeological puzzles, the Indo-European question, happily unanswered. A version of this paper was given at a 1994 meeting, on ‘Language, culture and biology in prehistoric central Eurasia’—its title a reminder that the biological view of Indo-European may again be a growing interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 17 publications
1
22
0
6
Order By: Relevance
“…In addition to championing a multi‐disciplinary approach to the prehistory of eastern Central Asia, we have re‐examined the claims of Indo‐European origins of Tarim Basin peoples. Our comparative work has generally shown that the narrative espoused by Mallory and Mair (2000), Barber (1999), Anthony (1995) and others, i.e. that the famous mummies are the progeny of ‘proto‐Celtic’‘Europeans’ from the Pontic Steppe who migrated thousands of kilometres across two vast mountain ranges and the entire Eurasian Steppe just to settle on the outskirts of one of the most inhospitable deserts in the world, is not the only interpretation for these data.…”
Section: Epiloguementioning
confidence: 66%
“…In addition to championing a multi‐disciplinary approach to the prehistory of eastern Central Asia, we have re‐examined the claims of Indo‐European origins of Tarim Basin peoples. Our comparative work has generally shown that the narrative espoused by Mallory and Mair (2000), Barber (1999), Anthony (1995) and others, i.e. that the famous mummies are the progeny of ‘proto‐Celtic’‘Europeans’ from the Pontic Steppe who migrated thousands of kilometres across two vast mountain ranges and the entire Eurasian Steppe just to settle on the outskirts of one of the most inhospitable deserts in the world, is not the only interpretation for these data.…”
Section: Epiloguementioning
confidence: 66%
“…This may not be the case. Although there are claims for horse domestication as early as 4500 BC for Iberia and the Eurasian steppe, the earliest undisputed evidence are chariot burials dating to Ϸ2000 BC from Krivoe Ozero (SintashtaPetrovka culture) on the Ural steppe (36,37,38). Burial, textual, and͞or iconographic evidence shows that by 1250 BC, chariots were widespread from Greece to China (37,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…But objections include that the reconstructed Proto-Indo-European lexicon has a strong bias toward domesticated animals rather than crops (81,82) and that reconstructed ProtoIndo-European words relating to wheels and wheeled vehicles suggest (some would say "prove") late Indo-European origins around the time of the invention of the wheel (ϳ4000 B.C.) (76). Even we two authors of this paper have differing views on this issue.…”
Section: Examples Of Specific Language Familiesmentioning
confidence: 91%
“…One hypothesis views Proto-Indo-European as having been spoken in the steppes north of the Black Sea by horse-riding nomadic pastoralists, whose supposed domestication of the horse and invention of the wheel around 4000 B.C. enabled them to expand militarily (74)(75)(76). But objections include that horse domestication and riding may not have begun until thousands of years later (77); that it is hard to understand ( perhaps even inconceivable) how steppe pastoralists could have imposed their language on so much of Europe west of the steppes (78); and that even linguists who reject glottochronology agree that Indo-European languages (including Anatolian) are so different from one another that their divergence probably began before 4000 B.C.…”
Section: Examples Of Specific Language Familiesmentioning
confidence: 99%